Effects of Storage Time on Total Protein and Globulin Concentrations in Bovine Fresh Frozen Plasma Obtained for Transfusion. (12th February 2015) - Proverbio, D.; Spada, E.; Baggiani, L.; Bagnagatti De Giorgi, G.; Roggero, N.; Belloli, A.; Pravettoni, D.; Perego, R.
Abstract : To evaluate the effects of storage conditions on total protein (TP) and globulin fractions in fresh frozen bovine plasma units prepared and stored for transfusion, TP and globulin fractions were evaluated in fresh plasma and at 1 month and 6 and 12 months after blood collection in plasma stored at −20°C. Significant differences in concentrations were found in the median concentration of total protein (P = 0.0336 ), between 0 months and 1 month (P = 0.0108 ), 0 and 6 months (P = 0.0023 ), and 0 and 12 months (P = 0.0027 ), in mean concentration (g/dL) of albumin (P = 0.0394 ), between 0 months and 1 month (P = 0.0131 ), 0 and 6 months (P = 0.0035 ), and 0 and 12 months (P = 0.0038 ), and beta-2 fraction (P = 0.0401 ), between 0 and 6 months (P = 0.0401 ) and 0 and 12 months (P = 0.0230 ). This study suggests that total gamma globulin concentration in bovine frozen plasma is stable for 12 months at −20°C. Total protein, ALB, and beta-2 fraction have significantly different concentrations (g/dL) when compared to prestorage. This study has shown IgG protein fraction stability in bovine fresh frozen plasma collected for transfusion; therefore, bovine fresh frozen plasma seems to be suitable for the treatment of hypogammaglobulinemia (failure of passive transfer) in calves when stored for 12 months at −20°C.